Implementation of HRIS (Human Resource Information System) in Enhancing Efficiency and Effectiveness of Technology Management - Rachmat Setiawibawa; Eriski Prawira; Theresia Dwi Siwi (Proceedings Series of Educational Studies, 2023)
This article discusses the application of HRIS (Human Resource Information System) in technology management to improve efficiency and effectiveness. HRIS is an information system that helps manage employee data, administrative processes, employee development, and communication within an organization. By using HRIS, organizations can automate routine tasks, improve access to information, and make decisions based on accurate data. HRIS implementation is also faced with challenges such as limited resources and changes in organizational culture, but with the right strategy, its benefits can be optimized in technology management.